2015
DOI: 10.1155/2015/269610
|View full text |Cite
|
Sign up to set email alerts
|

An Animal Model Using Metallic Ions to Produce Autoimmune Nephritis

Abstract: Autoimmune nephritis triggered by metallic ions was assessed in a Long-Evans rat model. The parameters evaluated included antinuclear autoantibody production, kidney damage mediated by immune complexes detected by immunofluorescence, and renal function tested by retention of nitrogen waste products and proteinuria. To accomplish our goal, the animals were treated with the following ionic metals: HgCl2, CuSO4, AgNO3, and Pb(NO3)2. A group without ionic metals was used as the control. The results of the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…Although, other metals were also positively associated with ANA, the associations were weak or close to null. Lead was the only metal examined in our study with toxicological literature supporting the association [19,69]. However, a recent epidemiological analysis by Dinse et al [16] found no association between blood lead in NHANES and ANA among men and women, a result which is inconsistent with those of the present study.…”
Section: Discussioncontrasting
confidence: 92%
“…Although, other metals were also positively associated with ANA, the associations were weak or close to null. Lead was the only metal examined in our study with toxicological literature supporting the association [19,69]. However, a recent epidemiological analysis by Dinse et al [16] found no association between blood lead in NHANES and ANA among men and women, a result which is inconsistent with those of the present study.…”
Section: Discussioncontrasting
confidence: 92%
“…We previously showed the presence of mercuric sulfides/selenides and other undetermined materials in skin biopsies of patients with EPF using autometallography and electron microscopy analysis . It has previously been demonstrated that ionic metals including HgCl 2 and CuSO 4 may cause kidney damage mediated by immune complexes in Long–Evans rats …”
Section: Discussionmentioning
confidence: 99%
“…The autoimmunity associated with environmental pollutants such as heavy metals is a phenomenon that has been studied widely, and a strong body of epidemiological and experimental evidence suggests that exposure to mercury, lead, and other metals could be associated with the development of autoimmunity. Animal models and in vitro studies have contributed to a better understanding of the molecular mechanisms by which metallic pollutants can induce immune dysregulation [2].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, metallic pollutants such as lead may affect the hydrophobic centres of proteins or may disrupt disulfide bridges or salt bridges and modify secondary or tertiary structures. The effect of metals on proteins can be predicted by determining the sites of adhesion dependent on metal ions or MIDAS [2]. In sum, conformational changes in a protein could increase its antigenicity, favouring immunologic tolerance breakdown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation